Analysis Of Time Waste In The X Woven Sarong Production Process Using Waste Assessment Model At Pt X - Laxmi Ratnaningsih; Enny Aryanny (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
PT X is a textile manufacturing company known as a prominent producer of woven sarongs. Among its various brands, the X sarong is the flagship product due to its high market value. Despite its large production scale, inefficiencies in the form of waste were detected within the production process. In this study, waste assessment model is applied to detect and categorize different kinds of inefficiencies or waste present in a process. The production flow is visualized using value stream mapping, and the value stream analysis tools are implemented to evaluate each process activity and identify its value added contribution. Root Cause Analysis (RCA) identifies the main causes of inefficiencies, and the 5W + 1H method is applied to formulate improvement strategies. WAM results indicate the highest to lowest waste percentages are: overproduction (22%), defects (20%), inventory (19%), transportation (15%), motion (13%), waiting (8%), and overprocessing (4%). Based on the proposed improvements, 14 non-value-added activities were eliminated, reducing total activities from 133 to 114 and cutting the process time by 139 minutes—from 3,853 to 3,714 minutes. Following the improvements, the Value Stream Mapping (VSM) analysis reveals a rise in Process Cycle Efficiency (PCE), improving from 67.5% to 70%, demonstrating a positive impact in minimizing waste and enhancing production efficiency.